Reply to "Tolerogenic insulin peptide therapy precipitates type 1 diabetes" - Daniel, Carolin; Weigmann, Benno; Von Boehmer, Harald (Journal of Experimental Medicine, 2017)
In this issue of JEM, Bergman et al. (https://doi.org/10.1084/jem.20160471) challenge the data published in our previous JEM paper on the preventive effect of tolerogenic vaccination with a strong agonist insulin mimetope in type 1 diabetes. Here, we provide a response to these data and suggest that appropriate subimmunogenic conditions are required to induce Foxp3+ regulatory T cell conversion.
EVALuna2:33899